Data encryption technology based on cloud and terminal collaboration - Guorong LIU; Dongxin LIU; Laifu WANG; Jun SHEN; Huamin JIN (Dianxin kexue)
With the fast increasing computing and storage capability,the intelligent terminal has gradually became the most important personal information assistant,and the data security of the terminal has turned to be essential for customers.Data encryption is a basic component of security assurance,but currently the mainstream technology scheme has a series of drawbacks,such as high technical cost.Therefore,a data encryption scheme based on cloud and terminal collaboration was proposed to promote the security of keys and data files.